2012
DOI: 10.1007/s11430-011-4356-1
|View full text |Cite
|
Sign up to set email alerts
|

Primary dolostone formation related to mantle-originated exhalative hydrothermal activities, Permian Yuejingou section, Santanghu area, Xinjiang, NW China

Abstract: The Permian Lucaogou Formation is an important hydrocarbon source rock in the Junggar, Turpan, and Santanghu basins in Xinjiang, NW China. For the first time, dolostones associated with mantle-originated exhalative hydrothermal fluid flows are discovered in Yuejingou section in the Santanghu Basin area. They include dolomicrite, doloarenite, and a small amount of dolorudite, and are finely (0.05-0.15 cm thick) interlaminated with lime micrite and dolomicritic analcime laminites. Alkali feldspar and analcime gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…7. Dolomites in this study have positive δ 13 C PDB and negative δ 18 O PDB values, similar to those of the two representative hydrothermal-sedimentary dolostones in China, the Cretaceous dolostones in the Jiuquan Basin (Wen et al 2013) and the Permian dolostones in the Santanghu Basin (Liu et al 2012;Jiao 2017). The δ 18 O PDB values of the studied dolostones are in the same range as those of the hydrothermal dolostones in the Jiuquan Basin, in Sardinia in Italy (Boni et al 2000), and in the Western Canada Sedimentary Basin (Al-Aasm 2003).…”
Section: Carbon and Oxygen Isotopessupporting
confidence: 75%
See 2 more Smart Citations
“…7. Dolomites in this study have positive δ 13 C PDB and negative δ 18 O PDB values, similar to those of the two representative hydrothermal-sedimentary dolostones in China, the Cretaceous dolostones in the Jiuquan Basin (Wen et al 2013) and the Permian dolostones in the Santanghu Basin (Liu et al 2012;Jiao 2017). The δ 18 O PDB values of the studied dolostones are in the same range as those of the hydrothermal dolostones in the Jiuquan Basin, in Sardinia in Italy (Boni et al 2000), and in the Western Canada Sedimentary Basin (Al-Aasm 2003).…”
Section: Carbon and Oxygen Isotopessupporting
confidence: 75%
“…Among the paragenetic minerals associated with dolomite in this study, analcime (Zheng et al 2003;Liu et al 2010Liu et al , 2012Wen et al 2013), albite (Zheng et al 2003;Liu et al 2010;Zhang et al 2010) and chalcedony (Tao et al 2016) have all been reported in hydrothermalsedimentary rock studies. Given the diverse genetic types of analcime and scarce reports of buddingtonite, these two minerals are analysed further.…”
Section: Paragenetic Mineralssupporting
confidence: 54%
See 1 more Smart Citation
“…The biggest difference between biomineralization and general mineralization lies in the participation of bio-macromolecular metabolism, cells, and organic matrix. The product of biomineralization, namely, biominerals, can be carbonate, phosphate, sulfate, sulfide, silicate, hydroxide or oxide, and involve different species of cations such as calcium, magnesium, iron, and/or manganese [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In the process of bacterially induced mineralization, microorganisms can release metabolic products to react with metal ions in the environment, and the process usually results in the subsequent precipitation of mineral crystals [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Calcium carbonate minerals at Earth's surface conditions include the common polymorphs calcite, aragonite, and vaterite, and the less common hydrated phases of monohydrocalcite (CaCO 3 •H 2 O) and ikaite (CaCO 3 •6H 2 O) [15][16][17][18][19][20][21][22][23][24][25][26][27]. It has been reported that monohydrocalcite is metastable compared with calcite and aragonite at all temperatures and pressures [28].…”
Section: Introductionmentioning
confidence: 99%